Comparison of Fenol-Kloroform Method and Mini-Prep CTAB Method for Chili (Capsicum annum L.) Plant DNA Isolation - Sri Okta Handayani; Dwi Hilda Putri (Jurnal Serambi Biologi, 2021)
Chili (Capsicum annum L.) is the most popular horticultural commodity in Indonesia. This high level of interest must be accompanied by an increase in the quality and quantity of chili production. One way to increase the quality and quantity of chilies is through plant breeding. Genetic variation analysis is one of the success factors in plant breeding. DNA isolation is the first step in analyzing genetic variation. There are various methods of plant DNA isolation, but DNA isolation methods using the fenol-kloroform method and CTAB mini-prep have not been widely reported. In this study, a comparison of the DNA isolation method of chili plants was carried out with the least DNA acquisition and contamination. This study used accessions of Capsicum annum L. (Cibinong03). The results of the qualitative evaluation study on confirmation of DNA samples were that there were no DNA bands found in the 0.8% agaorasa gel electrophoresis results, this result was inversely proportional to the results of the CTAB mini-prep method which produced DNA band bands in chilli accessions.